Synergistic Effects of Management Turnover and Financial Distress: An Investigation of Auditor Switching Moderation on Company Value - Taufik Hidayat; Rina Nurjanah; Murni Rahayu; Dede Puspa Pujia (Universitas Negeri Padang, 2026)
This study addresses the research problem of fluctuating company value in the manufacturing sector amidst the post-pandemic recovery, specifically examining whether internal governance shifts and financial pressures influence investor perception. The research objective is to analyze the impact of management turnover and financial distress on company value, with auditor switching as a moderating variable. Using a purposive sampling method, 32 manufacturing companies listed on the Indonesia Stock Exchange were selected, resulting in 160 observations over the 2020-2024 period. The analytical method employed was panel data regression using the Random Effect Model (REM), preceded by Chow, Hausman, and classical assumption tests. The key empirical results indicate that management turnover has no significant effect on company value. Conversely, financial distress and auditor switching exhibit a significant positive impact independently. These findings suggest that the market interprets distress as a